국립한글박물관 소장 「유가사지론」 제66권(초조장본)․제20권(재조장본)의 文字異同과 판본 성격에 대한 연구 - 류부현 (서지학연구, 0(88), 2021)
본 연구는 국립한글박물관 소장 「유가사지론」 제66권(초조장본)과 제20권(재조장본)의 판본 성격과 원문의 문자이동(文字異同) 관계를 밝혀보기 위한 것이다. 본 연구의 결과를 요약하면 다음과 같다. 첫째, 「유가사지론」 제66권의 판본 대조를 통해 밝혀진 문자이동은 37개이고, 이 문자이동은 13가지의 유형으로 정리․분석되었다. 그 결과 조성장은 개보장 수정본을 저본으로 삼아 복각된 것이고, 초조장은 개보장 원본을 저본으로 삼아 수정․복각된 다음 보각[매목]하여 수정된 것이며, 재조장은 개보장 원본을 저본으로 삼고 수정․복각된 것으로 판단되었다. 둘째, 「유가사지론」 제20권의 판본 대조를 통해 밝혀진 문자이동은 10개이고, 이 문자이동은 3가지의 유형으로 정리․분석되었다. 그 결과 조성장은 개보장 원본을 저본으로 삼아 복각된 것이고, 재조장은 개보장 원본을 저본으로 삼고 수정․복각된 것으로 판단되었다. 셋째, 선행연구에서는 국립한글박물관 소장 「유가사지론」 제66권(초조장본)에 묵서(墨書)․주서(朱書)와 각필(刻筆)로 표시된 교정내용이 재조장에 반영되어 있는 것으로 이해하였는데, 본 연구에서는 재조장의 수정된 내용이 한글박물관 소장 초조장본 「유가사지론」의 묵서․주서와 각필로 표시된 교정 내용에 반영되어 있는 것으로 판단하였다. This study explores the relationships between the characteristics of the block books of volume 66 (Chojojangbon) and volume 20 (Jaejojangbon) of Yougasagiron owned by National Hangeul Museum and character difference of the original. The summary of the results is as follows. Firstly, the number of character difference revealed through block book comparing of volume 66 of Yougasagiron is 37 and it is organized and analyzed with 13 types. As a result, it is estimated that Josungjang is reprinted based on the correction of Gaebojang, Chojojang is corrected and reprinted based on the original of Gaebojang and then recorrected with a work of bogak (maemok), and Jaejojang is corrected and reprinted based on the original of Gaebojang. Secondly, the number of character difference disclosed through block book comparing of volume 20 of Yougasagiron is 10, and it is organized and analyzed with three types. According to this, it is thought that Josungjang is reprinted based on the original of Gaebojang, Jaejojang is corrected and reprinted based on the original of Gaebojang. Thirdly, it is considered that the corrections of Jaejojang are reflected on the corrected contents written with mukseo, juseo, and gakpil of the volume 66 of Yougasagiron of Chojojangbon owned by National Hangeul Museum unlike the existing study in which the corrections written with mukseo, juseo, and gakpil of the volume 66 (Chojojangbon) of Yougasagiron owned by National Hangeul Museum are regarded as being reflected on Jaejojang. KCI Citation Count: 0